A Note on Marine and Estuary Fish Habitat, Prices and Supply in Different Markets of Dhaka City (The Agriculturists, 2019)
This paper analyses the available marine fish of Bay of Bengal and other coastal areas of Bangladesh and its supply in Dhaka city. The data is collected from fish wholesalers of three big markets of the city: Jatrabari, Gabtoli and Kawran Bazar. The collected data was analyzed using MATHEMATICA to determine the numbers of ocean species, their size, price and source of the coastal areas in Bangladesh. The results are presented both graphically and in tabular form.The Agriculturists 2019; 17(1-2) 112-120